ANALISIS KINERJA KEUANGAN DAERAH DALAM PELAKSANAAN OTONOMI DAERAH DI KABUPATEN HULU SUNGAI UTARA - WEDIYA PUTERI; CHAIRUL SA'RONI (PPJP Universitas Lambung Mangkurat, 2019)
The purpose of this research is to find out the Regional financial performance in the implementation of regional autonomy in the Hulu Sungai Utara Regency. Data analyzed in the form of Realization of Regional Revenue and Expenditure Budget of Hulu Sungai Utara Regency measured by regional financial ratios include: regional independence ration and relationship patterns, fiscal decentralization degree ratio, effectiveness and efficiency ratio, income growth and relationship pattern.The result of the ratio analysis in this study can be seen that the Hulu Sungai Utara Regency for Independence is still not able to carry out regional autonomy for the level of PAD capability is still low and effecicency is still lacking and even thouhg the effectiveness is effective and the growth has also been positive.Keyword : Regional Autonomy, Independence, DDF, Effectiveness, Efficiency, Revenue Growth.